Morphological, chemical and biochemical characterization of St. John's Wort (Hypericum perforatum L.) hybrids - Stefanovits-Bányai, Éva (Acta Biologica Szegediensis, 2002)
After several years of inbreeding, we concluded that combination of advantageous properties of Hypericum perforatum lines is necessary. Two hybrids were established by reciproc crossing a d their populations have been tested in the second year. Concerning drug production, hybrid F9 exceeded both parents. In the case of hypericin content, crossing resulted in the manifestation of mother's effect. Hypericin content was higher in flowers, while POD accumulated mainly in leaves. Alterations of them in the mentioned parts proved to be inverse: the level of hypericin increased and that of the POD decreased from vegetative to flowering phase. The content of glucose and fructose changed by organs during ontogenesis, their ratio in flowers increased. There were significant differences among taxa investigated: parent 35 and hybrid F16 showed lower values of POD and glucose in average, which may be in connection with their weaker tolerance against wilt disease.